The boundary value problem for an ordinary linear half-order differential equation - Aliyev, N.; Rasulov, M.; Sinsoysal, B. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This study is devoted to the study of the solution of a boundary value problem for an ordinary linear differential equation of half order with constant coefficients. Using of the fundamental solution of the main part of the considered equation, we obtained the principal relations, from which we obtain the necessary conditions for the Fredholm property of the original problem. Further, using the Mittag-Leffler function, a general solution of the homogeneous equation is obtained. Finally, the problem under consideration is reduced to an integral Fredholm equation of the second kind with a non-singular kernel, i.e., the Fredholm property of the stated problem is proved.
Keywords: half-order equations; boundary value problem; fundamental solution; basic relation; integral equations; Fredholm property; Mittag-Leffler functions; general solution of a homogeneous half-order equation